Synthesis of 2,3-Unsaturated Alkynyl O-Glucosides from Tri-O-acetyl-d-glucal by Using Montmorillonite K-10/Iron(III) Chloride Hexahydrate with Subsequent Copper(I)-Catalyzed 1,3-Dipolar Cycloaddition - Melo, Valentina Nascimento; Dantas, Willyenne Marília; Camara, Celso Amorim; de Oliveira, Ronaldo Nascimento (Synthesis, 2015)
Two strategies were considered for the synthesis of 2,3-unsaturated O-glucosyl-1,2,3-triazoles. The first, involving reaction between tri-O-acetyl-d-glucal and triazole alcohols gave no stereoselectivity. A second strategy provided 2,3-unsaturated O-glycosides from glycals and alkynols through a Ferrier rearrangement; this method, employing montmorillonite K-10 doped with iron(III) chloride hexahydrate in dichloromethane afforded new glycosides in good to excellent yields within short times and with high α-stereoselectivities. Subsequently, the glucosides were coupled with 2-azido-1,4-naphthoquinone to produce a new series of 1,2,3-1H-triazolyl O-glucoside derivatives through a click reaction.
Keywords: rearrangements; triazoles; glycosides; alkynes; copper; click reactions